The effects of physician retirement on patient outcomes: Anticipation and disruption - ZHANG, Xuan (Institutional Knowledge at Singapore Management University, 2022)
The physician retirement rate in the United States is increasing as the population ages. I use an event study model allowing for anticipation to evaluate the effects of primary care physician (PCP) retirement on elderly adults’ health care utilization and quality of care. I find that, despite moderate anticipatory effects, PCP retirement results in an approximately $572 increase in total Medicare costs per beneficiary in the first 1.5 years post-retirement and an over 10% increase in detection of new chronic conditions. Heterogeneity analyses show that the increase in costs is disproportionately driven by the retirement of solo practitioners; Medicare beneficiaries with a retired PCP practicing in states with mandatory physician departure notice experience less disruption in care; and beneficiaries living in primary care health professional shortage areas experience greater disruption in care.